Effects of Trichoderma Species on the Growth of Fusarium Verticillioides (Bangladesh Journal of Botany, 2021)
Six biocontrol treatments viz., Trichoderma viride, Trichoderma virens, Trichoderma harzianum, T. harzianum + T. viride, T. harzianum + T. virens and T. viride + T. virens were evaluated to test the antagonism against Fusarium verticillioides under in vitro conditions. The maximum growth inhibition (90.6%) was recorded in consortium of T. harzianum + T. viride in dual culture technique . The volatile and non volatile compounds from the consortium of T. harzianum + T. viride also found best and suppressed the mycelial growth of F. verticillioides to the tune of 83.90 and 84.61 %, respectively.Bangladesh J. Bot. 50(2): 423-425, 2021 (June)